Preoperative radiotherapy: A paradigm shift in the treatment of breast cancer? A review of literature - Corradini, Stefanie; Krug, David; Meattini, Icro; Matuschek, Christiane; Bölke, Edwin; Francolini, Giulio; Baumann, René; Figlia, Vanessa; Pazos, Montserrat; Tonetto, Fabrizio; Trovò, Marco; Mazzola, Rosario; et al. (Critical Reviews in Oncology Hematology, 2019)
The standard of care for early-stage breast cancer (BC) consists of breast-conserving surgery followed by postoperative irradiation. Recently, the concept of changing the usual sequence of treatment components in BC RT has been investigated. Potential advantages of preoperative RT in BC include a possible tumor downstaging with improved surgical cosmetic outcomes, accurate tumor site identification and better target volume delineation. Furthermore, preoperative RT could serve as a tool for treatment stratification for de-escalation of treatments in the event of pathological complete response. The present literature review analyzed the available clinical data regarding the potential impact of preoperative RT. Overall, available clinical evidence of preoperative RT in BC remains limited, deriving mostly from retrospective case series. Nevertheless, the experiences prove the feasibility of the preoperative RT approach and confirm the efficacy in almost all analyzed studies, including experiences using higher prescription RT doses or RT in combination with systemic therapy.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Breast cancer; Local control; Neoadjuvant treatment; Outcome; pCR; Preoperative radiotherapy; Radiotherapy; Survival